PROBABILITY IN THE MODALITY CATEGORY OF THE ENGLISH AND KARAKALPAK LANGUAGES - Bayimbetova, M.B. (SCIENCE and SOCIETY, 2023)
The presence of wide probability in the manifestation of the modal category, of course, indicates that this category is a universal phenomenon and its study is of great importance for understanding the essence of a language construction. In this article, the author analyzes the relationships of the language to the most complex and comprehensive category of modality in English and Karakalpak, as well as the expression of the category of modality.